A novel ABCD1 gene mutation causes adrenomyeloneuropathy in a Chinese family. Issue 10 (26th September 2019) - Wang, Chao; Liu, Hongchao; Han, Bing; Zhu, Hui; Liu, Jingyao
Abstract: Background: Adrenomyeloneuropathy (AMN) is a rare genetic disease. In this study, a case of AMN was uncovered in a Chinese family. Methods: Clinical manifestations were collected and observed through medical records, physical examination, laboratory tests, and magnetic resonance imaging (MRI). Generation sequencing of the ABCD1 gene was performed, and the pedigree of the family was analyzed. Results: The proband suffered from adrenocortical insufficiency at 8 years old and presented with a slowly progressive gait disorder at 21 years old. Physical examination, laboratory tests, and MRI showed that he had adult‐onset AMN manifestations, including spasticity and hyperactive tendon reflexes with Hoffman and Babinski signs in the limbs, difficulty in performing the heel‐to‐shin test, hyperpigmentation, increased levels of adrenocorticotropic hormone and very long‐chain fatty acids, decreased levels of corticosteroid and serum gesterol, and salient atrophy of the cervical and thoracic spinal cord. DNA analysis revealed a missense variant, c.290A>C (p.His97Pro) in exon 1 of the ABCD1 gene, in the proband. Sanger sequencing confirmed that the proband's mother was heterozygous for the same variant. The ABCD1 gene mutation transmitted in an X‐linked inheritance manner. Conclusion: A novel missense mutation in the ABCD1 gene was identified in a Chinese family, which caused an unusual manifestation of adult‐onset AMN. This discovery is beneficial for the genetic counseling of patients with X‐linked adrenoleukodystrophy. Abstract : (a) We report a case of adrenomyeloneuropathy in a Chinese family. (b) DNA analysis revealed a missense variant c.290A>C (p.His97Pro) in exon 1 of the ABCD1 gene in the proband.